Heat-Insulating Materials Obtaining from Dispersive Screenings of Construction Sand; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Kazmina O. V. Olga Viktorovna; Duschkina M. A. Marija Alexejewna; Volland S.; Lebedeva E. (Chemical Technologies, 2014)
Title screen